Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Menganalisis Rangkaian Listrik Kelas X Jurusan Teknik Instalasi Tenaga Listrik Di SMK N 1 Tanjung Raya - Moh. Irvan Basith; Zulwisli Zulwisli; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research aimed to see whether there is a difference between learning outcomes using cooperative learning model Teams Games Tournament ( TGT ) with the learning outcomes using direct learning. This research is an experimental research, the researchpopulation is a class X student of the installation of Electric Power Engineering SMK Negeri 1 Tanjung Raya TA 2013/2014 . The sampling technique was done by using nonprobability sampling with purposive sampling . The data collected from the test results in the form of learning objective questions about as many as 35 points . Data were analyzed using Microsoft Excel to test homogeneity , normality , and hypothesis testing . From the results of research conducted tests on samples of both groups gained an average of learning outcomes for the experimental group the average value of the initial test was 49.1 and the average value of the final test is 81.8 with an increase of 32.7. For the control group the average value of the initial test was 52.2 and the average value of the final test is 72.2 with an increase of 20 . The results of the hypothesis by using Microsoft Excel found that tcount 5,960 > 1,671 ttable, so the alternative hypothesis (H1) is accepted or rejected the null hypothesis (H0). This means that the average significant learning outcomes experimental class higher than the average of the control class learning outcomes .